In-House Prepared High Fat Diet (HFD) Can Cause an Increase in Body Weights of Male Albino Wistar Rats in a Short Period of 2-3 Weeks (Medical Forum Monthly, 2024)
Objective: The current study was designed to evaluate the effects of the in-house prepared high fat diet (HFD) on body weights of rats.Study Design: Comparative, Experimental Study Place and Duration of Study: The study was conducted at Institute of Basic Medical Sciences (IBMS), Dow University of Health Sciences (DUHS), Ojha Campus, Karachi in a period of 2-3weeks.Materials and Methods: The study was conducted on 20 male albino Wistar rats which were randomized into 2 groups; each group containing 10 rats. HFD-fed rats were kept on in-house prepared HFD and water ad libitum throughout the study. While control / Non-HFD fed rats were kept on standard diet and water.Results: SPSS (version 16.0) was used in the study analysis. The mean difference in body weights of rats was analyzed by using ANOVA. The results are expressed as mean ± SD. The results report that there is statistically significant difference (P-value < 0.001) between HFD-fed and non HFD-fed groups.Conclusion: HFD-fed group gained significant weight when fed an in-house prepared diet in comparison to non HFD-fed group in 2-3 weeks.